Drama-based strategies for vocabulary development in young English learners in the western region of Saudi Arabia - Alelyani, Abdulaziz Ali Fayz; Alharbi, Mohammed Salim (Institute of Advanced Engineering and Science, 2025)
This study investigates the efficacy of drama-based methodologies in English vocabulary acquisition among young learners in Saudi Arabia, addressing a significant gap in the Saudi English as a foreign language (EFL) context. Employing a descriptive, quantitative research design, the study surveyed 137 English language instructors from the Jeddah Educational Directorate. The findings reveal that diverse dramatic activities yield substantial benefits in English language learning, particularly in vocabulary acquisition. Key advantages include enhanced motivation for contextual vocabulary usage, improved learner engagement, increased self-confidence, and enhanced communication skills. The study highlights the superiority of varied and engaging drama-based techniques, such as role-playing, over traditional methods in fostering a dynamic and conducive learning atmosphere. While acknowledging challenges like increased teacher preparation time and students’ initial reluctance towards active participation, the research concludes that drama-based instruction represents an effective pedagogical approach for teaching English vocabulary to young learners. The study proposes significant implications for educational policy, recommending the integration of drama-based English textbooks into the curriculum and the incorporation of drama techniques in teacher training programs. This research contributes valuable insights to ongoing discourse on innovative EFL teaching methodologies in the Saudi Arabian context.